Assessment of wear properties on low temperature molten salt bath nitriding on austenitic stainless steel. (2020) - Chaitanya kumar, B.; Sri Charan, P.; Jayakumar, Kanishkar; Alankrutha, D.; Sindhu, G.; Subbiah, Ram
Abstract: AISI 310 steel is an austenitic stainless steel used in applications like furnaces, house appliances, turbine parts, compressor parts. This project investigates on the wear behavior of AISI 310 steel treated with salt bath nitriding processes treated to different timing parameters like 60, 120, 180 min respectively. Wear test is conducted by using pin-on-disc apparatus for the both nitriding specimens for wear resistance with constant load and speed for the turbine applications. SEM observations were made for the changes in surface and macroscopic level. Hardness test is performed by using Vickers hardness test. The microstructure results shown that a white layer was observed in both nitriding processes. After nitriding time was increased white layer decomposed to chromium Nitride (CrN) phase. From Wear results it was observed that as load increases wear loss increases. It was observed that hardness increases with the nitriding time. X-ray diffraction results also confirmed the phases in nitrided specimens. With the test results, the specimens of salt bath and untreated were compared in order to determine better wear resistant specimen.